Toward Understanding Reciprocity in Community-University Partnerships: An Analysis of Theories of Power - Brandon Kliewer; Lorilee R. Sandmann; Jihyun Kim; Anthony Omerikwa (Adult Education Research Conference, 2010)
Reciprocity and mutuality are fundamental values and inherent goals of community-engaged partnerships. However, achieving reciprocal relationships demands an understanding of forms of power and differentials in power. With the work of major theorists and philosophers as its foundation, this paper provides a framework from which to analyze power as it relates to reciprocity in community engagement.